Hemophagocytic Lymphohistiocytosis: A Life Threatening Cytopenic Condition (Faridpur Medical College Journal, 2021)
Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening disorder that occurs in many underlying conditions in all age. This is characterized by unbridled activation of cytotoxic T lymphocytes, natural killer (NK) cells and macrophages resulting in raised cytokine level. Those cytokines and immune mediated injury occur in multiple organ systems. It may be primary and secondary. Primary HLH is familial, childhood presentation and associated with gene mutations. Secondary HLH is acquired, adulthood presentation that occurs in infections, malignancies inflammatory and autoimmune diseases etc. Clinical manifestations include fever, splenomegaly, lymphadenopathy, neurologic dysfunction, coagulopathy, features of sepsis etc. Laboratory investigation includes cytopenias, hypertriglyceridemia, hyperferritinemia, abnormal liver function, hemophagocytosis, and diminished NKcell activity. Treatment modalities include immunosuppressive, immunomodulatory agents, cytostatic drugs, T-cell antibodies, anticytokine agents and hematopoietic stem cell transplantation (HSCT). Besides those, aggressive supportive care combined with specific treatment of the precipitating factor can produce better outcome. With treatment more than 50% of children who undergo transplant survive, but adults have quite poor outcomes even with aggressive management.Faridpur Med. Coll. J. 2020;15(2): 98-102